2018
DOI: 10.1016/j.parint.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

First genetic evidence for the presence of the rumen fluke Paramphistomum epiclitum in Pakistan

Abstract: More than 70 species of the Superfamily Paramphistomoidea, have been identified in ruminants in different parts of the world. Most are pathogenic, causing amphistomosis. Adult flukes within this family have a predilection for the forestomach (rumen) or bile duct of the liver, where they may cause epithelial damage. Identification of adult Paramphistomum, Calicophoron, Gastrothylax and Fischoederius at the species level based on morphology requires specialised expertise, whereas molecular genetic marker analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
10
2
Order By: Relevance
“…The results are contrary to the report where P. cervi was closely related to Paramphistoma leydeni [11]. The genetic evidence for the existence of some other trematodes including P. epiclitum, Gigantocotyle explanatum, Fasciola hepatica, and Fasciola gigantica in Pakistan have been previously reported using 18S rRNA markers [1,20,33]. However, for the first time the amplification of 18S rRNA in this study revealed a molecular based evidence for P. cervi in Pakistan.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results are contrary to the report where P. cervi was closely related to Paramphistoma leydeni [11]. The genetic evidence for the existence of some other trematodes including P. epiclitum, Gigantocotyle explanatum, Fasciola hepatica, and Fasciola gigantica in Pakistan have been previously reported using 18S rRNA markers [1,20,33]. However, for the first time the amplification of 18S rRNA in this study revealed a molecular based evidence for P. cervi in Pakistan.…”
Section: Discussioncontrasting
confidence: 99%
“…The Paramphistomidae family comprises numerous species of Paramphistomes (commonly known as rumen fluke) trematodes infecting rumen and reticulum of ruminants globally [19,7]. More than seventy species of the superfamily Paramphistomoidea have been identified in different geographical regions [1]. Ruminant's paramphistomiasis (rumen fluke disease) are due to the pathogenic activities of Paramphistoma species of the genus Paramphistomum [32].…”
Section: Introductionmentioning
confidence: 99%
“…The first location of the juvenile trematodes in the ruminant host is the small intestine where the parasites feed on the intestinal mucosa. Following further growth, the parasites migrate upwards to the reticulum and rumen where they spend the rest of their adult lives, shedding eggs that contaminate snail habitats (Ali et al, 2018; Dinnik & Dinnik, 1954; Soulsby, 1982). Amphistomosis is globally distributed, but the highest prevalence has been reported from tropical and sub‐tropical regions, particularly Africa, Asia, Australia, Eastern Europe and Russia (Dube & Aisien, 2010; Gupta, Singh, & Dutt, 1978; Horak, 1971; Huson et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of rumen fluke infections in ruminants has been widely reported across several European countries such as the UK (Jones et al ., 2017), Ireland (Toolan et al ., 2015) and the Netherlands (Ploeger et al ., 2017), and on other continents such as Oceania (Cauquil et al ., 2016) and Asia (Ali et al ., 2018). In America, the presence of rumen flukes in ruminants has been reported in Peru (Pinedo et al ., 2010) and Mexico (Ojeda-Robertos et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%